Perspective review: lessons from successful clinical trials and real-world studies of systemic therapy for metastatic pheochromocytomas and paragangliomas - Camilo Jimenez; Rene Baudrand; Thomas Uslar; Daniel Bulzico (Therapeutic Advances in Medical Oncology)
Pheochromocytomas and paragangliomas (PPGLs) are orphan tumors with the potential to spread to distant organs such as the lymph nodes, the skeleton, the lungs, and the liver. These metastatic tumors exhibit high rates of morbidity and mortality due to their frequently large tumor burden, the progression of the disease, and the excessive secretion of catecholamines that lead to cardiovascular disease and gastrointestinal dysmotility. Several molecular drivers responsible for the development of PPGLs have been described over the last 30 years. Although therapeutic options are limited, substantial progress has been made in the recognition of effective systemic therapies for these tumors. Successful clinical trials with radiopharmaceuticals such as high-specific-activity meta-iodobenzylguanidine and tyrosine kinase inhibitors such as cabozantinib and sunitinib have been recently published. This review will discuss the results of these studies and their impact on current clinical practices. In addition, this review will provide valuable information on how to design clinical trials to treat patients with metastatic PPGLs with novel medications.